TAFSIR QUR’AN SURAT LUQMAN AYAT 12 – 19 SUBSTANSINYA DENGAN PESAN MORAL LUQMAN AL-HAKIM DALAM PENDIDIKAN ISLAM - Eka Abdul Hamid; Rika Wanda Nuraeni Zakiya (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2020)
This study aims to: 1) find out Luqman Al-Hakim's moral message contained in Q.S. Luqman verses 12 to 19. 2) know how Islamic education is from a moral aspect, 3) know the moral message of Luqman Al-Hakim in Islamic education. This type of research is qualitative research using a library research approach/literature review, with the primary data being the Alquran Surah Luqman verses 12 to 19, and secondary data is the Al-Maroghi interpretation by Ahmad Mustofa Al-Maraghi, the interpretation of M. Quraisy Shihab by M Quraish Shihab and Ibn Kathir's commentary by Imam Abi Al-Hasan Ali Bin Ahmad, books, and scientific works, journals, and various other sources, related to research. The results showed that there are four moral messages contained in Surah Luqman verses 12 to 19 according to Islamic education. The four moral messages are in accordance with the basis of Islamic education, namely instilling aqidah in children, teaching them to be grateful and devoted to Allah and their parents, accustoming them to doing good deeds from an early age, and teaching them noble morals and the ethics of interacting with others.